2019
DOI: 10.1080/1331677x.2019.1645710
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric contagion effect from the U.S. stock market around the subprime crisis between 2007 and 2010

Abstract: This study employed Enders and Siklos asymmetric co-integration frameworks, including the momentum threshold autoregressive (M-TAR) and logistic smooth transition co-integration (LSTC) models, to investigate whether contagion effects had existed in international stock markets by using the changes in the asymmetric co-integration relationships between the U.S. S&P 500 Index and a total of 23 markets in Asia, Europe, and America during the subprime crisis. The main findings demonstrated that the subprime crisis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 104 publications
(167 reference statements)
1
9
0
3
Order By: Relevance
“…Literature pointed out that contagion effects exist when negative impacts occurred during the crisis. Kao, Zhao, Ku, and Nieh (2019) found out the homogeneity or non-heteroscedasticity of information transmission in international stock markets increased significantly during the period of the subprime crisis. In our model, the total contagion effect is divided into contagion effect and threshold effect, and it is expected to increase significantly during the crisis, in the following three hypotheses.…”
Section: Hypothesesmentioning
confidence: 97%
See 1 more Smart Citation
“…Literature pointed out that contagion effects exist when negative impacts occurred during the crisis. Kao, Zhao, Ku, and Nieh (2019) found out the homogeneity or non-heteroscedasticity of information transmission in international stock markets increased significantly during the period of the subprime crisis. In our model, the total contagion effect is divided into contagion effect and threshold effect, and it is expected to increase significantly during the crisis, in the following three hypotheses.…”
Section: Hypothesesmentioning
confidence: 97%
“…The literature focuses on the contagion effects between stock markets in different countries. In the empirical literature, a number of different methods have been used to measure how shocks spread internationally, such as: Heteroscedasticity-adjusted correlation coefficient test (Forbes & Rigobon, 2002); ARCH and GARCH (Kao, Zhao, Ku, & Nieh, 2019), cointegration techniques (Nieh et al, 2011;Nieh et al, 2012), probit model, TAR (Jawadi, Louhichi, & Ameur, 2013) and TAR-GARCH (Chiang & Doong, 2001). The traditional symmetric co-integration tests of Engle and Granger (1987) The traditional symmetric co-integration tests also rarely consider the issue of "non-linear" or "asymmetric" characteristics.…”
Section: Empirical Research Of Contagions Effectsmentioning
confidence: 99%
“…Over the periods, global stock markets have become more interlinked and the possibilities of trade & financial linkages between the countries are considered to be the major determination of stock exchange integration (Xiao & Dhesi, 2010). The global financial crises of 2008 attracted the researchers' attention towards the interconnectedness of financial markets, when the collapse of US stock market adversely affected the financial and stock markets of many countries from almost all parts of the world (Kao et al, 2019). This interconnectedness of financial markets was also evident during the Asian Crisis in 1997 and the terrorist attacks on World Trade Centre in 2001.…”
Section: R M B Rmentioning
confidence: 99%
“…Prior studies suggested that cross-market correlation volatility during a financial crisis is heightened [13,15,18]. We used the U.S.-China trade war as the significant economic event in this study.…”
Section: Introductionmentioning
confidence: 99%